Analysis of Aggressive Behavior in Early Children - Sari, Siti Erlina; Sit, Masganti (Education Achievement: Journal of Science and Research, 2024)
The teacher's strategy in this research is the effort made by the teacher to achieve the goal of fostering and handling aggressive behavior in early childhood which is a problem in the learning process at school. Aggressive behavior in this research is the child's attitudes, actions and words when the child interacts with other people which shows anger and emotional outbursts as well as harsh words such as scolding and shouting at other people expressed by the child which can disrupt the learning process at school. The aim of this research is to determine teachers' strategies for dealing with aggressive behavior in early childhood. This research is qualitative research with the nature of a case study and is described descriptively. Data collection techniques in this research are observation, interviews and documentation. The data analysis technique in this research uses a model, namely data reduction, data presentation and drawing conclusions. The results of this research are about the teacher's strategy in dealing with children's aggressive behavior, namely the teacher embracing the child when the child takes action. aggressive, persuade teachers and give good advice to children, teachers must also be gentle in dealing with children who behave aggressively. Based on this research case study, it is known that the strategies implemented by the teacher can reduce children's aggressive behavior well using the Book Antiqua font size.